SWOT Analysis of Nursing Clinic Professional Career Ladder System (SJKP2K) in Military Hospital Jakarta - Bela Pertiwi; Rr Tutik Sri Hariyati; Siti Anisah (International Journal of Nursing and Health Services (IJNHS), 2018)
Nursing managers must have a strong directing function towards the Professional Clinic Nurse Career Ladder System (SJKP2K). This is to improve the quality of nursing care that will be provided by nurses to patients. The military hospital in Jakarta already has the standard of planning, guidelines and SOP regarding the SJKP2K, but based on the authors' observations for two weeks in one of the rooms in the hospital, the results show that the SJKP2K implementation is not optimal. This problem then analyzed using the SWOT Analysis followed by scoring and weighting through an Internal Factors Evaluation (IFE) and External Factors Evaluation (EFE) matrix analysis. The sum of the scores of each matrix ??then poured into the IE (Internal and External) matrix to determine the position of the SJKP2K strengths. The calculation result between IFE and EFE in IE matrix shows that SJKP2K is in area V, which means that SJKP2K is in hold and maintain stage so that market penetration and product development strategies are needed so that SJKP2K requires development both in quality and quantity.